ANALISIS CONTENT IKLAN BIDANG AKUNTANSI DENGAN PERSYARATAN KETERAMPILAN AKUNTAN - Herlina Pusparini; Nurabiah Nurabiah; Yusli Mariadi (Jurnal Aplikasi Akuntansi, 2022)
The purpose of this study is to find out what professional skills are most needed by accountants based on an analysis of job advertisements. This type of research is descriptive research with content analysis approach. The subjects is 14 trusted job search sites in Indonesia. The results of the study stated that the order of qualification of accountant skills required by companies listed on credible job search sites in Indonesia includes 1) technical skills 2) interpersonal skills 3) personal skills 4) intellectual skills and 5) organizational skills. The results of this study indicate that mastery of accounting basics and mastery of technology in the form of accounting software are hard skills that must be possessed by accounting graduates, followed by soft skills such as communication and English, ability to adapt and work under pressure, critical and logical thinking, and ability to work according to deadlines.